Perlindungan Hukum terhadap Teknologi Non-Fungible Token (NFT) sebagai Identitas Karya Intelektual - Hapsari, Recca Ayu; Aprinisa, Aprinisa; Putri, Rachel Anzani (Amsir Law Journal, 2023)
Non-Fungible Token (NFT) is a new digital platform that helps artists empower their work with easy access and secure tools and methods that can be used easily. The problem is how is the legal protection of NFT technology as an intellectual work identity? How is the NFT form a solution in protecting Indonesia’s intellectual property rights in a review of Law Number 28 of 2014 concerning Copyright? The research method uses a juridical-empirical approach. By using primary and secondary legal materials obtained from literature and field studies by means of observation and interviews. The results of research on legal protection of NFT technology as the identity of intellectual works explain that in Indonesia itself there are no specific regulations that strictly regulate NFT as objects of legal protection, considering that NFTs are born through a process of creation (which is followed up with conversion/printing) where NFT is basically electronic data. NFTs become objects of digital artwork so that NFTs can be categorized as creations in accordance with the provisions of Article 1 Number 3 of Law Number 28 of 2014 concerning the Copyright Act and regulated in the provisions of Law Number 19 of 2016 concerning Information and Electronics, and Regulations Government Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions. The NFT form can be a solution in protecting Intellectual Property Rights in Indonesia when viewed from Law Number 28 of 2014 concerning Copyright that the certainty of ownership rights in every digital artwork which is then converted into NFT has its own code or token. In addition, this form will be difficult to imitate from various forms of plagiarism in intellectual property. ___ Referensi Buku dengan penulis: Ramli, Ahmad M. (2010). Cyber Law dan Haki dalam Sistem Hukum Indonesia. Bandung: Refika Aditama. Saidin. (2015). Aspek Hukum Hak Kekayaan Intelektual (Intellectual Property Rights). Depok: Rajagrafindo Persada. Sari, I. N., dan Putranto, W. A. (2023). Perlindungan Arsip Vital dan Penanganan Arsip Pascabencana. Yogyakarta: UGM Press. Soekanto, Soerjono., dan Mamudji, Sri. (2001). Penelitian Hukum Normatif: Suatu Tinjauan Singkat. Jakarta: PT Radja Grafindo Persada. Artikel jurnal: Adinata, M. R., dan Hapsari, R. A. (2022). Tinjauan Yuridis Perlindungan Konsumen terhadap Masyarakat yang Melakukan Fintech Peer-To-Peer Lending atau Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi (LPMUBTI) Dalam sebuah Aplikasi Pinjaman Online (Julo)(Studi Penelitian: Otoritas Jasa. Case Law, 4(1), 21-38. Benuf, K., dan Azhar, M. (2020). Metodologi Penelitian Hukum sebagai instrumen Mengurai Permasalahan Hukum Kontemporer. Gema Keadilan, 7(1), 20-33. Dewi, Ni Kadek Risma Setya Cahyani, dan Sukihana, Ida Ayu. (2022). Perlindungan Hukum terhadap Karya Seni Dalam Bentuk Non-Fungible Token (NFT). Jurnal Kertha Wijaya, 11(4), 906–918. Gidete, B. B., Amirulloh, M., dan Ramli, T. S. (2022). Pelindungan Hukum atas Pelanggaran Hak Cipta pada Karya Seni yang dijadikan Karya Non Fungible Token (NFT) pada Era Ekonomi Digital. Jurnal Fundamental Justice, 1-18. Hariri, M. R., Ramli, A. M., dan Ramli, T. S. (2023). Tinjauan Hukum Praktik Komersialisasi Lagu dan/atau Musik Melalui Non-Fungible Token (NFT) Oleh Para Musisi di Indonesia. COMSERVA Indonesian Jurnal of Community Services and Development, 2(11), 2645-2657. Lubis, U. S. (2020). Hak Kekayaan Intelektual Sebagai Objek Wakaf. Iuris Studia: Jurnal Kajian Hukum, 1(1), 31-38. Manurung, P., dan Angelita, E. (2013). Perlindungan Hukum Terhadap Hak Cipta Atas Karya Cipta Digital di Indonesia. Premise Law Journal, 1(2), 1-19. Noor, M. U. (2021). NFT (Non-Fungible Token): Masa Depan Arsip Digital? Atau Hanya Sekedar Buble?. Pustakaloka, 13(2), 223-234. Purwanda, S. (2022). Hilangnya Hak Eksklusif Tanaman Rempah Asli Indonesia. Pangadereng: Jurnal Hasil Penelitian Ilmu Sosial dan Humaniora, 8(1), 137-152. Saroh, S., Achmad, L. I., Hamdan’Ainulyaqin, M., dan Edy, S. (2023). Analisis Transaksi Digital Non Fungible Token (NFT), Sebagai Instrumen Investasi dan Jual Beli Aset Virtual Menurut Perspektif Ekonomi Islam (Studi Transaksi Digital Virtual Asset NFT pada Platform OpenSea. io). Jurnal Ilmiah Ekonomi Islam, 9(1), 378-386. Sudjana, S. (2022). Efektivitas Penanggulangan Pembajakan Karya Cipta Dalam Perspektif Sistem Hukum. Res Nullius Law Journal, 4(1), 77-99. Sulistianingsih, D., dan Kinanti, A. K. (2022). Hak Karya Cipta Non-Fungible Token (NFT) Dalam Sudut Pandang Hukum Hak Kekayaan Intelektual. Krtha Bhayangkara, 16(1), 197-206. Wang, Q., Li, R., Wang, Q., dan Chen, S. (2021). Non-Fungible Token (NFT): Overview, Evaluation, Opportunities and Challenges. arXiv preprint arXiv:2105.07447. Wiradirja, I. R. (2013). Pelanggaran Hak Moral Atas Karya Cipta Dalam Penerbitan Elektronik. LITIGASI, 14(1), 1662-1697.